The influence of talent management on organizational performance of Malaysian public agencies - Mat Zin, Sakinah; Ibrahim, Norshamsiah; Nik Md Salleh, Nik Sarina; Hamid, Roseliza; Setapa, Mariam (Journal of Islamic, Social, Economics and Development, 2026)
The study examines the influence of talent management practices, specifically talent acquisition and talent retention on organizational performance within public agencies in Malaysia. It draws upon the Resource-Based View (RBV) Theory as its underlying theoretical framework. Data were collected through a self-administered questionnaire distributed to 385 employees, who were selected using a convenience sampling technique. The hypotheses were tested using multiple regression analysis. The findings indicate that talent management has a positive and significant effect on organizational performance, whereby both talent acquisition and talent retention demonstrate strong and statistically significant relationships with performance outcomes. This study represents the first empirical investigation of talent management practices and organizational performance within Malaysian public agencies. Consequently, the results offer valuable insights for public sector officers, as they underscore the importance of implementing effective talent management practices to enhance organizational performance and organizational effectiveness.